GENDERED LINGUISTICS IN THE URBAN INFORMAL ECONOMY OF ZAMBIA (Proceedings of the World Conference on Women’s Studies, 2026)
The informal economy has become a lifeline for urban populations in Zambia, particularly in cities like Lusaka and Ndola. This growth is a direct response to widespread economic hardships and significant rural-urban migration. Within this vibrant sector, the intersection of language and gender remains a critically understudied area. Prevailing language policies often reflect colonial legacies, marginalizing the rich indigenous languages that are central to daily life and economic survival in the informal economy. This paper addresses this gap by investigating how language functions as a resource, shaping linguistic choices and generating economic value. The primary objective was to examine the divergent linguistic strategies employed by women and men and to assess how these gendered language practices influence their economic outcomes. Employing a qualitative, ethnographic approach, this study utilized observations, in-depth interviews, and sociolinguistic surveys in selected urban markets. The analysis is grounded in Language as a Resource Theory and Gender and Language Theory. Findings indicate that both women and men deploy a range of linguistic strategies, blending local urban varieties to suit specific economic activities, with multilingualism serving as a key tool for economic gain. The study further reveals how language use both reflects and perpetuates gender disparities in these economic settings. These insights challenge existing language frameworks in Zambia and point to a pressing need for more inclusive policies that recognize linguistic diversity and creativity.
Keywords: Informal economy; Gendered linguistics; Zambia